Project appraisal: a revival is long overdue - Bell, Clive (Working paper, 2017)
This paper makes the case for the systematic appraisal of public sector projects using shadow prices as the signals of social scarcities. In so doing, it attempts to redress the balance between estimating inputs and outputs, central though that task is, and valuing them correctly. The account of how to estimate shadow prices for this purpose pays particular attention to the social discount rate and how to treat uncertainty at both the project and economy-wide levels. There follows an illustration of the ideas and apparatus in practice using an evaluation of India's large rural roads programme (PMGSY) in connection with a World Bank loan. A discussion of the more general uses of shadow prices in evaluating decisions in the public sector is complemented by a series of proposals for the implementation of systematic procedures for project appraisal in government and international donors.